Duration dependence, lagged duration dependence, and occurrence dependence in individual employment histories - Markus Niedergesäss (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
This paper investigates the form and magnitude of a variety of state dependence effects for prime-aged men in Germany. I differentiate between three labor market states: employment, unemployment, and out of labor force. Results indicate that all forms of state dependence are present in the data, in particular, there is strong duration dependence in employment and unemployment. Furthermore, past unemployment experiences are scarring and make future unemployment more likely while past employment experiences help to find new employment, but do not help to remain employed. Simulations are conducted in order to investigate the effects of possible interventions in the labor market.
urn:nbn:de:bsz:21-opus-60246
Keywords: C33; C41; J64; 330; state dependence; transition data; event history analysis; unobserved heterogeneity; Erwerbsverlauf; Arbeitslosigkeit; Event Study; Hysteresis; Dauer; Männer; Schätzung; Deutschland